Evolução cenozóica da área de Longroiva-Vilariça (NE Portugal) - Cunha, P. Proença (2000)
In the Longroiva-Vilariça area, the identification of Cenozoic lithostratigraphic units, the sedimentology and the characterization of its geometric relations with tectonic structures allowed the interpretation of the palaeogeographic main stages: 1) the greenwhitish Vilariça Arkoses (Middle Eocene to Oligocene ?) represent proximal sediments of a very low gradient drainage towards the eastern Spanish Tertiary Duero Basin; 2)Quintãs Formation (late Miocene ?) are brown-reddish coloured piedmont alluvial deposits, correlative of important vertical displacement (western tectonic block relative uplift) along the NNE-SSW indent-linked strike-slip Bragança-Vilariça-Longroiva fault zone, interpreted as a reactivated deep hercynian fracture, with left-lateral movement; 3) the red Sampaio Formation (Gelasian-early Pleistocene ?)was interpreted as downhill conglomeratic deposits related with important overtrusting along this fault zone (the definition of the present-day narrow graben configuration) and correlative of the atlantic hydrographic incision stage beginning; 4) conglomeratic terraces (middle and late Pleistocene ?); 5) alluvial plains and colluvial deposits (Holocene).